KOPING RELIGIUS PADA ORANG TUA ANAK BERKEBUTUHAN KHUSUS - Malitsa Giovanna Tahitu (IAKN Ambon, 2022)
This study was conducted to find out how parents deal with the phenomenon of having a child with special needs, their difficulty in accepting each process, and the support mechanisms used to deal with the situation. Phenomenological research design used with 6 parents. Phenomenologically obtained data were analyzed with the support of MAXQDA 11. The three aspects discussed in this study are the difficulty of the acceptance process, coping strategies, and religious coping. The difficulty aspect of self-acceptance discusses feelings of shock, fear of losing a child, disappointment, self-blame, loneliness, lack of husband support, the impact of a negative environment, concern for the child's future, and hopelessness. Aspects of the coping strategy address family support and environmental concerns. Whereas the religious coping aspect discusses accepting what God gives us, destiny, fear of God, blessings from God, believing in God by surrendering, squashing..